Corpos filtrados: ansiedade social por aparência, autoestima e insatisfação corporal em adolescentes nas redes sociais - uma leitura junguiana - Mendes, Lara Martinez (2023)
In order to analyze the use of selfies, their filters, and editions linked to self-esteem, and social anxiety arising from self-image and body satisfaction in teenagers, a descriptive, quantitative, and cross-sectional study was carried out in a private school in Curitiba. The Participants were 61 teenagers between the ages of 13 and 19 years who ranged from the ninth year of elementary school to the third year of high school, 60.7% of the participants were male and 39,3% female. The instruments used were 1) User profile Questionnaire 2) Rosenberg Self-Esteem Scale 3) Social Appearance Anxiety Scale. The results showed a significant difference between the genders, all the female participants declared using filters, tending to use them more than the male gender, as well as showing greater social anxiety about appearance. Most participants said they use filters for fun, to improve, or, to correct their appearance. Those who reported using filters showed greater anxiety about appearance and greater body dissatisfaction than those who did not, however, there was no significant difference in the selfesteem of both groups. Considering image filters a contemporary way of presenting oneself to others, this study aims to broaden the understanding of the virtual world idealized by young people and the representation of the persona in the construction of identity